Benthic drivers of structural complexity in coral reefs across a tropical-subtropical transition zone - Wu, Meng-Hsin Morris; Ribas-Deulofeu, Lauriane; Liu, Chia-Hung Eric; Nozawa, Yoko; Denis, Vianney (Frontiers in Marine Science, 2025)
This study examines changes in structural complexity of coral reefs in a tropical-subtropical transition zone and identifies the benthic factors influencing their patterns. Structure-from-motion photogrammetry was used to create digital elevation models (DEMs) and generate orthomosaic images for 25 study sites distributed across five coral reef regions along the east coast of Taiwan. A selection of 11 complexity metrics was used to capture the overall variations while benthic composition was described. It was found that fine-scale complexity decreases with increasing latitude as the dominance of intricate coral morphologies is replaced by plain zoanthids and crustose coralline algae. Coarse-scale complexity, on the other hand, increases in subtropical reefs with large boulders and unstable substrates, reflecting unique topographic features in regions of lower coral cover and accretion. Latitudinal variation in complexity is mostly driven by the turnover in benthic composition. These changes alter the available habitats and could ultimately affect the overall biodiversity and functionality of reef systems. Understanding transitional patterns is particularly important as ocean warming may lead to a reorganization of existing benthic communities in tropical-subtropical transition zones.